A new system for digital image acquisition, storage and presentation in an accident and emergency department. Issue 4 (1st July 2001) - Clegg, G R; Roebuck, S; Steedman, D J
Abstract : Objectives —To develop a computer based storage system for clinical images—radiographs, photographs, ECGs, text—for use in teaching, training, reference and research within an accident and emergency (A&E) department. Exploration of methods to access and utilise the data stored in the archive. Methods —Implementation of a digital image archive using flatbed scanner and digital camera as capture devices. A sophisticated coding system based on ICD 10. Storage via an "intelligent" custom interface. Results —A practical solution to the problems of clinical image storage for teaching purposes. Conclusions —We have successfully developed a digital image capture and storage system, which provides an excellent teaching facility for a busy A&E department. We have revolutionised the practice of the "hand-over meeting".